Trends and comparisons of diabetes burden in China and the world from 1990 to 2021,with forecasts to 2050:a systematic analysis of the global burden of disease study 2021 - Chenqing Liu; Yun Li; Nan Wang; Yandong Wu; Jiaqi Liu; Mengjie Ding; Shuhan Liu; Yibing Hao; Ying Wu; Shaopeng Liu (Diabetology & Metabolic Syndrome)
Abstract Background Diabetes is a major global public health issue. This study investigated the trends in the age—and gender—specific burden of diabetes in China and worldwide from 1990 to 2021, and predicted the prevalence of diabetes in 2050. Methods Using publicly available data from the Global Burden of Disease (GBD) database from 1990 to 2021, we comprehensively applied Joinpoint regression and age—period—cohort (APC) analysis to reveal the epidemiological characteristics, conducted decomposition analysis to identify the driving factors of burden changes, and used the autoregressive integrated moving average (ARIMA) model to project the disease burden of diabetes from 2022 to 2050. Results From 1990 to 2021, both in China and globally, the age—standardized incidence rate (ASIR), age—standardized prevalence rate (ASPR), and age—standardized disability—adjusted life year rate (ASDR) of diabetes showed an upward trend. In contrast, China's age—standardized mortality rate (ASMR) of diabetes decreased, while the global ASMR increased. The average annual percentage changes (AAPC) of China's ASIR, ASPR, ASMR, and ASDR were 1.29, 1.76,− 0.30, and 0.76% respectively, compared with 1.74, 2.10, 0.25, and 1.05% for the global diabetes burden. Conclusions In China, the incidence, prevalence, and Disability-Adjusted Life Years (DALYs) of diabetes increased, while the mortality rate decreased. It is projected that by 2050, the number of diabetes patients in China will reach 84.01 million, and globally, it will reach 1038.2 million. Given China's large population and the trend of population aging, it is essential to formulate targeted prevention and control strategies to address the challenge of diabetes.